Inhibition of Cd accumulation in grains of wheat and rice under rotation mode using composite silicate amendment. Issue 61 (1st November 2019) - Li, Yang; Liang, Xuefeng; Huang, Qingqing; Xu, Yingming; Yang, Fang
Abstract : Composite silicate amendment had significant immobilization effects for phytoavailable Cd in the soil and inhibitory effect on the accumulation of Cd in crop grains under in field-scale remediation under wheat/rice rotation mode. Abstract : The accumulation of heavy metals in soils and crops jeopardizes human health, and thus remedying soil and ensuring food safety have attracted wide concern. In this study, composite silicate was employed as an amendment to inhibit cadmium (Cd) accumulation in the grains of wheat and rice in an upland/paddy rotation mode in field-scale remediation. The composite silicate amendment (CSA) at a dosage of 0.2–0.8% decreased the Cd concentration in wheat grains in the first growing season of upland mode by 7.5–58.3% compared with CK, and decreased the Cd concentration in brown rice by 38.7–58.1% in the second season of paddy mode. The minimum values satisfy the Chinese National and International Standards. The results confirmed the inhibitory effect of CSA on the accumulation of Cd in crop grains. CSA increased the soil pH obviously and enhanced the sorption of Cd on soil particles by 14.6–56.2%, and declined the DTPA- and HCl-extractable Cd concentrations in the soil by 16.2–49.5% and 23.8–75.6%, respectively. Furthermore, CSA decreased the exchangeable Cd fraction by 21.5–41.6% in the sequential extraction. The immobilization effect was retained in both growing seasons in terms of Cd concentration in the crop grains and extractable Cd concentration in the soil. CSA had a negligible effect on the normal growth of wheat and rice and the available Zn and Cu concentration in the soil, indicating its environmental friendliness. Considering its low cost and abundant reserves, CSA can be recommended as an immobilization amendment for Cd-polluted paddy soil in wheat/rice rotation mode.